Digitalized Instructional Materials in Creative Writing based on Technological Pedagogical Content Knowledge - Manalastas, Jared P. (International Journal of Humanities and Education Development (IJHED), 2020)
The main objective of the study was essentially focused on determining the effective ways in teaching creative writing among the Grade 11 Humanities and Social Sciences (HUMSS) students based on the Technological Pedagogical Content Knowledge (TPACK) in utilizing and developing digitalized instructional materials. A Quasi-Experimental research design was specifically utilized for one group shot. The creative writing teacher employed the digitalized resources in teaching creative writing covered for the semester after administering pretest to improve the writing skills of the students. Data collection was limited to pretest and posttest scores of the subjects using Paired T-test dependent among the students taking up the creative writing subject. This research concluded that there is significant difference in teaching creative writing of HUMSS students using digitalized materials. Using various tools available online and electronic resources can help and enrich students’ creative writing abilities towards independent learning. Thus, writing opportunities can take place everywhere both in the classroom and at home